2007
DOI: 10.1111/j.1741-3737.2006.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximity and Contacts Between Older Parents and Their Children: A European Comparison

Abstract: Using data from the 2004 Survey of Health, Ageing and Retirement in Europe, this article continues and extends recent cross‐national research on proximity and contacts of older parents to their children. In addition to a brief description of the geography of families in 10 continental European countries, determinants of intergenerational proximity and contacts are examined. Even when microlevel factors are controlled for, the Mediterranean peoples continue to exhibit closer family relations than their northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
412
0
31

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(460 citation statements)
references
References 43 publications
(86 reference statements)
17
412
0
31
Order By: Relevance
“…Although grandparents play different roles in different regimes, there is little evidence of a general decline in the strength of intergenerational relations (e.g., Hank, 2007;Kohli and Albertini, 2008;Gray, 2005). The literature also stresses the fact that grandparenting is predominantly driven by the needs of the adult children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although grandparents play different roles in different regimes, there is little evidence of a general decline in the strength of intergenerational relations (e.g., Hank, 2007;Kohli and Albertini, 2008;Gray, 2005). The literature also stresses the fact that grandparenting is predominantly driven by the needs of the adult children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…frequent is the contact, particularly at short and medium distances (Lee et al 1990;Bengtson and Roberts 1991;Grundy and Shelton 2001;Lawton et al 1994;Smith 1998;Glaser and Tomassini 2000;Hank 2007). The provision of care and support for family members also takes place less often when the distance between the places of residence is greater (Daatland and Lowenstein 2005;De Jong Gierveld and Fokkema 1998;Knijn and Liefbroer 2006;Joseph and Hallman 1998;Tomassini et al 2003).…”
mentioning
confidence: 99%
“…Previous studies based on SHARE have also shown that elderly old people in the Scandinavian countries are more satisfied with their social network despite less frequent contact [9,10], and report less loneliness despite a higher prevalence of living alone and other indicators of assumed social community [11]. One explanation could be that in the universal welfare regime the family may have a complementary and more positive role in addition to the more daily-based support from public providers.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-national comparisons reveal closer intergenerational contacts in Southern and Eastern Europe, with a family-based welfare model, compared to the Scandinavian universal welfare regime [9]. Even though intergenerational contacts are less frequent in the Scandinavian countries and more old people live alone, several studies report greater satisfaction with the social network as compared to countries in Southern and Eastern Europe [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation